Some problems of the legal support for monitoring of local governance’s activities in administrative servicesdelivery - Mokritska, Anna; Petrykiv, Anna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
Fundamental aspects for successful citizen-based monitoring of local governance’s activities in administrative services-delivery have been presented. Some issues of the legal support for monitoring of local governance’s activities in administrative services-delivery are given.